1986
DOI: 10.1210/jcem-62-1-217
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology of Propylthiouracil (PTU) in Pregnant Hyperthyroid Women: Correlation of Maternal PTU Concentrations with Cord Serum Thyroid Function Tests*

Abstract: Previous studies have characterized the pharmacology of propylthiouracil (PTU) in normal and hyperthyroid subjects, but there is little information available regarding PTU pharmacokinetics in pregnant hyperthyroid women. We investigated the serum PTU response to an oral dose of PTU in six hyperthyroid pregnant women both ante- and postpartum. The serum PTU profile during the third trimester of pregnancy was qualitatively similar to that in nonpregnant subjects, but serum PTU concentrations were consistently lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(31 citation statements)
references
References 9 publications
1
29
0
1
Order By: Relevance
“…Furthermore, cord PTU levels were found to be higher than maternal concentrations in patients treated with PTU until term [15]. There were also no identified differences in thyroid hormone and TSH concentrations in cord blood at birth between patients treated with CBZ/MMI and PTU [16], although this study was underpowered to detect modest differences.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, cord PTU levels were found to be higher than maternal concentrations in patients treated with PTU until term [15]. There were also no identified differences in thyroid hormone and TSH concentrations in cord blood at birth between patients treated with CBZ/MMI and PTU [16], although this study was underpowered to detect modest differences.…”
Section: Resultsmentioning
confidence: 99%
“…A study showed that transfer rates across the placenta were independent of the perfusate protein concentration, and this might be due to highly efficient placental extraction of the unbound drug (23). Cord PTU levels were higher than maternal concentrations in hyperthyroid pregnant patients treated with PTU until term (24). In addition, there were no differences in thyroid hormone and TSH concentrations in cord blood at birth between the MMI-and the PTU-treated newborn (25).…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of spontaneous or inherited ACC is approximately 1:2000 births (2) and is limited in the vast majority of cases to the scalp (Table 1 ); the ACC rate after maternal MMI treatment, however, remains unknown. PTU and MMI cross the placenta similarly (9,10) . However, the theoretical risk for PTU is lower owing to higher levels of drug binding to serum proteins (11) .…”
Section: Discussionmentioning
confidence: 99%